Perinatal characterization of multiple pregnancy in Cienfuegos city from 2001 to 2002 - Mariam Zam; Alberto Jorge Fernández; Gabriel Jiménez González; Alexis Díaz Brito; Cristóbal Torres González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
Background: Multiple pregnancy is the gestation of more than one fetus in the uterine cavity, in this case two of them. This kind of pregnancy is considered a high obstetric risk due to its high rate in perinatal morbimortality. Objectives: to assess the morbimortality rate behavior in multiple pregnancy of two fetuses in Cienfuegos city. Methods: A descriptive retrospective study about multiple pregnancy of two fetuses was carried out in the University Hospital ¨Dr: Gustavo Aldereguía Lima¨; in Cienfuegos city from 2001 to 2002. This kind of pregnancy with more than 28 weeks of gestation as well as the deliveries taken place in the above mentioned hospital constituted the sample of this investigation. The influence of this kind of pregnancy in the main perinatal morbimortality indicators was analyzed. Results: out of the total of 9 556 birth, 95 of them were of twins for a 0, 9 per cent of incidence. The increment of the maternal weight was over 12 kg. and was associated with the higher weight of the newborn baby. 61 % of the mothers presented obstetric diseases. The most frequent were preterm labor, hypertension, and premature rupture of the membrane. Cesarean delivery had the 51 % for both deliveries and its main causes were; malposition of one or both fetuses, soft parts dystocia and hypertension in the pregnancy process. The most frequent illnesses in the perinatal morbimortality were low weight at birth, fetal late antepartal death and the umbilical cord procidentia.